Tyr-199 and charged residues of pharaonis Phoborhodopsin are important for the interaction with its transducer. - Sudo, Yuki (2002)
pharaonis Phoborhodopsin (ppR; also pharaonis sensory rhodopsin II, psRII) is a retinal protein in Natronobacterium pharaonis and is a receptor of negative phototaxis. It forms a complex with its transducer, pHtrII, in membranes and transmits light signals by protein-protein interaction. Tyr-199 is conserved completely in phoborhodopsins among a variety of archaea, but it is replaced by Val (for bacteriorhodopsin) and Phe (for sensory rhodopsin I). Previously, we (Sudo, Y., M. Iwamoto, K. Shimono, and N. Kamo, submitted for publication) showed that analysis of flash-photolysis data of a complex between D75N and the truncated pHtrII (t-Htr) give a good estimate of the dissociation constant K(D) in the dark. To investigate the importance of Tyr-199, K(D) of double mutants of D75N/Y199F or D75N/Y199V with t-Htr was estimated by flash-photolysis and was approximately 10-fold larger than that of D75N, showing the significant contribution of Tyr-199 to binding. The K(D) of the D75N/t-Htr complex increased with decreasing pH, and the data fitted well with the Henderson-Hasselbach equation with a single pK(a) of 3.86 +/- 0.02. This suggests that certain deprotonated carboxyls at the surface of the transducer (possibly Asp-102, Asp-104, and Asp-106) are needed for the binding.